Frontilines Readiness in Facing Attacks of Mysterious Acute Hepatitis in Indonesia: A Qualitative Approach - Dewangga Gegap Gempita; Agusdini Banun; Pamungkas, Rian Adi (International Journal of Nursing and Health Services (IJNHS), 2023)
Background: Frontliners are currently the leading pillar in dealing with various health cases that arise in Indonesia. several health cases that have become epidemics or pandemics provide significant lessons on how frontliners are prepared to deal with health problems. one of them is an attack of Mysterious Acute Hepatitis. the ability of frontliners to deal with attacks of acute hepatitis will be one of the keys to the readiness of health workers and hospitals in dealing with the development of the disease. Objective: The study aimed to explore frontliners' readiness regarding knowledge, skills, mental health in dealing with Mysterious Acute Hepatitis at Mustika Medika Hospital . Method: A qualitative study with phenomenology approach was applied in this study. In-depth interviews and Focus Group Discussion (FGD) techniques were carried out in collecting research data. Informants in this study were 12 people taken from nurses, midwives, doctors and also representatives of hospital management. Result: The results found that four themes described the frontliners readiness in facing the attacks of mysterious acute hepatitis including: 1) lack of Understanding of Mysterious Acute Hepatitis; 2) readiness of self-protection; 3) anxiety about the high transmission and also the death rate of acute hepatitis; 4) hospital readiness both in terms of facilities and infrastructure